Facile synthesis of BSCF perovskite oxide as an efficient bifunctional oxygen electrocatalyst - Azad U.P.; Singh M.; Ghosh S.; Singh A.K.; Ganesan V.; Singh A.K.; Prakash R. (My University, 2025)
We present a facile way to synthesize BSCF by using glycine-nitrate auto-combustion followed by annealing at different conditions, which work as high-performance bifunctional electrocatalyst for oxygen evolution (OER) as well as oxygen reduction (ORR) reactions in alkaline solution with comparatively better efficiency for OER. Annealing condition plays an important role towards catalytic performance due to morphological control and surface composition. Although, there is no significant change in onset potentials but these catalysts afford a current density >10 mA cm−2 at the potential of 1.65 V for oxygen evolution reaction and a current density >2.5 mA cm−2 at the potential of 0.009 V for oxygen reduction reaction with respect to RHE in 0.1 M KOH. The underlying mechanism for ORR and OER as well as catalytic activity differences were understood with the help of different analytical characterization techniques. © 2018 Hydrogen Energy Publications LLC